Near‐Infrared Light‐Driven Three‐Dimensional Soft Photonic Crystals Loaded with Upconversion Nanoparticles. Issue 9 (16th March 2022) - Qiu, Yaqi; Yang, Yanzhao; Valenzuela, Cristian; Zhang, Xuan; Yang, Mengyuan; Xue, Pan; Ma, Jiazhe; Liu, Ziwei; Wang, Ling; Feng, Wei
Abstract: Endowing advanced functional three‐dimensional (3D) nanostructures with remote and dynamic controllability is currently in the spotlight of soft‐matter photonics research. Herein, the near‐infrared (NIR) light‐driven reversible and dynamic photonic bandgap modulation of a soft photonic crystal, i.e., blue phase liquid crystals (BPLCs) with 3D nanostructures, is demonstrated through the integration of judiciously designed core‐shell upconversion nanoparticles (UCNPs) and a novel axially‐chiral azobenzene‐based molecular photoswitch. The UCNPs exhibit high UV/vis emissions upon irradiations with 808 nm NIR light, and the intensity ratio of UV/vis luminescence can be facilely modulated through changing the excitation power. With the UCNPs as NIR‐to‐UV/vis light nanotransducers, the chiral molecular photoswitch shows reversible photoisomerization upon modulating the 808 nm NIR light intensity. Furthermore, NIR light‐driven BPLCs loaded with the photoswitch and UCNPs are demonstrated, in which the photonic reflection can red‐shift toward a longer wavelength under 808 nm light irradiation with high‐power density and the blue‐shift took place at lower power density with the same wavelength of light. This work may provide new insights into the large‐scale fabrication of 3D photonic nanostructures with tailorable functionalities toward emerging applications of soft‐matter photonics and future integrated communication technologies. Abstract : Near‐infrared photoactive soft photonic crystals, i.e., blue phase liquid crystals with 3D nanostructures, are demonstrated through the integration of judiciously designed core‐shell upconversion nanoparticles and a novel axially chiral azobenzene‐based molecular photoswitch. This work can offer new insights into the development of 3D photonic nanostructures with tailorable functionalities for diverse applications such as soft‐matter photonics, adaptive camouflage, and beyond.